Airflow limitation in COPD is associated with increased left ventricular wall stress in coincident heart failure. Issue 9 (September 2015) - Alter, Peter; van de Sand, Kirsten; Nell, Christoph; Figiel, Jens H.; Greulich, Timm; Vogelmeier, Claus F.; Koczulla, Andreas R.
Abstract: Background: COPD and heart failure occur with a considerable coincidence. Beside well-known mechanisms of increased right heart load in COPD, dedicated changes of the left ventricle (LV) are ill-defined and the question remains, whether specific interactions exist beyond common shared risk factors. Methods: LV wall stress was calculated based on cardiac magnetic resonance imaging in 28 patients with COPD (GOLD I to III) and coexistent heart failure (LVEF 42 ± 19%) due to non-ischaemic and ischaemic cardiomyopathy. Results: LV enddiastolic (p = 0.048) and endsystolic wall stress (p = 0.034) increased from GOLD stage I to III. Reduced FEV1 was correlated with increased enddiastolic (p = 0.0210) and endsystolic LV volume (p = 0.0413) and with increased enddiastolic (p = 0.0161) and endsystolic LV wall stress (p = 0.0315), respectively. Increased wall stress was associated with a decreased FEV1/FVC ratio. Conclusions: The severity of airflow limitation in COPD was correlated with increased LV wall stress. It is suggested that respiration in pulmonary obstruction is associated with an increased negative intrathoracic pressure when compared with normal lung function, which is transmitted to the heart and increases the transmural pressure gradient and thereby distending forces on the heart. Increased ventricular wall stress is known to be associated with a broad variety of unfavourable consequences, which should be taken into account to contribute to a worse prognosis in COPD. Graphical abstract: The pressure gradient transmitting distending forces on the left ventricular (LV) wall is influenced by intraventricular luminal pressure [Plum] and surrounding thoracic pressure [Pthoracic]. Respiration with airflow limitation is assumed to increase the negative pleural pressure and thereby the transmural pressure gradient. Airflow limitation in COPD was correlated with increased LV wall stress in coincident heart failure. Highlights: COPD and heart failure occur with a considerable coincidence. Influences of COPD and the left ventricle are ill-defined. Left ventricular wall stress was calculated based on chamber volumes and myocardial mass as assessed by CMR. Airflow limitation was associated with increased left ventricular wall stress. Increased ventricular wall stress should be taken into account to contribute to a worse prognosis in COPD.